2021
DOI: 10.1002/med.21809
|View full text |Cite
|
Sign up to set email alerts
|

Trends in targeted delivery of nanomaterials in colon cancer diagnosis and treatment

Abstract: Colon cancer is an adenocarcinoma, which subsequently develops into malignant tumors, if not treated properly. The current colon cancer therapy mainly revolves around chemotherapy, radiotherapy and surgery, but the search continues for more effective interventions. With the advancement of nanoparticles (NPs), it is now possible to diagnose and treat colon cancers with different types, shapes, and sizes of NPs. Nanoformulations such as quantum dots, iron oxide, polymeric NPs, dendrimers, polypeptides, gold NPs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 225 publications
0
27
0
Order By: Relevance
“…The biocompatibility of cobalt oxide nanoparticles can also be improved by forming composite materials with other materials, for example, using silica as the protective shell of cobalt oxide nanoparticles, which significantly in-creases their biocompatibility [44]. In addition, similar to what Khan et al reported [49], the biocompatibility and bioavailability of cobalt oxide nanoparticles can also be improved through the combined use of cobalt oxide nanoparticles and other nano preparations. Additionally, cobalt oxide nanoparticles obtained by different preparation methods have different biocompatibility.…”
Section: Biocompatibility Of Cobalt Oxide Nanoparticlesmentioning
confidence: 73%
“…The biocompatibility of cobalt oxide nanoparticles can also be improved by forming composite materials with other materials, for example, using silica as the protective shell of cobalt oxide nanoparticles, which significantly in-creases their biocompatibility [44]. In addition, similar to what Khan et al reported [49], the biocompatibility and bioavailability of cobalt oxide nanoparticles can also be improved through the combined use of cobalt oxide nanoparticles and other nano preparations. Additionally, cobalt oxide nanoparticles obtained by different preparation methods have different biocompatibility.…”
Section: Biocompatibility Of Cobalt Oxide Nanoparticlesmentioning
confidence: 73%
“…Colon cancer is a type of adenocarcinoma that can develop into a malignant tumor if treated improperly. Colon cancer is the third leading cause of cancer-related deaths worldwide ( Khan et al., 2022 ). The occurrence of colon cancer is related to numerous factors, including genetic factors, environmental factors, infections with bacteria such as Helicobacter pylori , and changes in gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is one of the three leading causes of cancer-related deaths worldwide ( Khan et al., 2022 ). According to recent statistics, there are approximately 376,300 new cases of colon cancer annually ( Chen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy could induce infertility problems in patients. Moreover, non-specific delivery of chemodrugs to off-target sites can ultimately cause unwanted side effects such as gastrointestinal toxicity, liver toxicity, and hematologic disorders [ 5 , 6 ]. Notably, tumor recurrence occurs in 30–50% of CC patients after chemotherapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%